Novel EIF5A-USP6 Gene Fusion in Nodular Fasciitis Associated With Unusual Pathologic Features: A Report of a Case and Review of the Literature - Lenz, Jiri; Michal, Michael; Svajdler, Marian; Ptakova, Nikola; Lenz, David; Konecna, Petra; Kavka, Miroslav (The American journal of dermatopathology, 2020)
Nodular fasciitis (NF) is a benign self-limiting soft tissue lesion that has long been considered a reactive process. Recently, however, the USP6 gene rearrangement has been discovered, and the neoplastic nature of this tumor was suggested. Since then, many fusion partners of the USP6 gene have been reported, with the MYH9 gene as the most common. In this article, we describe a case of NF with a novel EIF5A-USP6 gene fusion associated with unusual pathological features. A 41-year-old healthy woman with a painful, rapidly growing subcutaneous mass on the left forearm with a size of 0.8 cm is presented. A soft tissue fragment measuring 1 cm was surgically excised. Owing to positive surgical margins, re-excision was performed, yielding another 2-cm fragment. The lesion was extensively histologically investigated. Immunohistochemical and molecular-genetic analysis, namely fluorescence in situ hybridization, next-generation sequencing, and reverse transcriptase-polymerase chain reaction, were also performed. Histology revealed a dermally located, mitotically active myofibroblastic proliferation with myxoid areas that ulcerated the overlying epidermis. One atypical mitotic figure was also found. The lesion showed positive immunohistochemical staining with smooth muscle actin, whereas S100 protein and CD34 stains were negative. Using fluorescence in situ hybridization, the USP6 gene rearrangement was detected and subsequent analysis using the Archer fusionPlex Sarcoma kit revealed a novel EIF5A-USP6 gene fusion. In the appropriate clinicopathological context, the detection of USP6 gene rearrangement is extremely useful when diagnosing NF, significantly reducing the risk of misdiagnosis and inappropriate overtreatment.
Keywords: Fasciitis; Oncogene Fusion; dospělí; RNA-Binding Proteins; proteiny vázající RNA; lidé; Female; Peptide Initiation Factors; onkogenní fúze; fasciitida; iniciační faktory; thiolesterasa ubikvitinu; Ubiquitin Thiolesterase; Adult; ženské pohlaví; Humans